Stamped Hispanic Amphorae from Roman Dacia - Grumeza, Lavinia (Rei Cretariae Romanae Fautorum Acta, 2022)
Approximately 60 stamped amphorae have been published from Roman Dacia, part of these being featured on Dressel 20 amphorae, found in Tibiscum (M MAC SVR), Arcidava (C IV P, PLEGONT), Aiton (VIRGIN), and Apulum (DA(?) OPTATI, VINT). In addition to these stamps, a number of anepigraphic sherds from Dressel 20 amphorae are known from Angustia, Sarmizegetusa, Cingşor, Tibiscum, and Romula. Two further pieces coming from Sarmizegetusa and Apulum feature tituli picti inscribed in red dye: Λ I S and LEG XIII G. The sites in Roman Dacia which produced Dressel type 20 amphorae are without exception dated between the early 2nd century AD and the 60’s of the same century. Furthermore a large part of these settlements are characterized by a considerable military presence. The situation is similar in the case of Pannonia Inferior and Moesia Superior, where the majority of Baetican amphorae also come from military sites. Statistically speaking, the number of Hispanic amphorae in Dacia is quite small, even in comparison to Moesia and Pannonia, probably due to the fact that Dacia was conquered only at the beginning of the 2nd century AD, and only 50/60 years later the commercial routes were already shifting.